Thoughtfully reflective decision making and the accumulation of capital: bringing choice back in - Paternoster, Raymond (Journal of quantitative criminology, 2011)
In this paper we relate a particular type of decision making, thoughtfully reflective decision making (TRDM) in adolescence, to successful and unsuccessful life outcomes in young adulthood. Those who are thoughtfully reflective in their decision making are more likely to consider possible alternative routes to goal attainment, weigh the costs and benefits of those alternatives, and critically revisit the decision once made to examine what went well and what went wrong. We also argue that what mediates the effect of TRDM on later life outcomes is the accumulation of capital. Those who use better decision making practices are more likely to recognize the resources provided by and make the necessary investments to accumulate human, social and cultural capital. These notions are theoretically linked to conceptions of criminal offenders as both rational planners and decision makers and as fully human agents. Using data from the Add Health data set, our hypotheses are largely confirmed. Those who are higher in TRDM as adolescents were more likely to have enrolled in or graduated from college, to be in better physical health, are more involved in civic and community affairs, less likely to commit criminal acts, use illegal drugs and be involved in heavy drinking as adults. TRDM is also positively related to the accumulation of human, social and cultural capital. Finally, a substantial part of the effect of TRDM on young adult outcomes was mediated by capital accumulation. The implications of these findings for future theory and research are discussed.